The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3389/fmolb.2016.00069
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding RNA Regulation of Dopamine Signaling in Diseases of the Central Nervous System

Abstract: Dopaminergic neurotransmission mediates a majority of the vital central nervous system functions. Disruption of these synaptic events provokes a multitude of neurological pathologies, including Parkinson's, schizophrenia, depression, and addiction. Growing evidence supports a key role for noncoding RNA (ncRNA) regulation in the synapse. This review will discuss the role of both short and long ncRNAs in dopamine signaling, including bioinformatic examination of the pathways they target. Specifically, we focus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…For example, Ago2, not 1, 3, and 4, is downregulated in brain lysates from encephalomyelitis mice, the expression level of several miR-NAs, including let-7a-5p, let-7e-5p, let-7f-5p, 106b-5p, 144-3p, and 188a-5p, display a significant reduction (Lewkowicz et al, 2015), suggesting that Ago2 is involved in the etiology of CNS diseases (Savas et al, 2008). Deficiency of Ago2 in D2R neurons relieves self-administration of cocaine due to the declined content of miRNAs in the mouse striatum (Schaefer et al, 2010), revealing a vital role of Ago2 in the treatment of CNS diseases (Carrick et al, 2016). Here, we found that nociceptive behavior caused the decrease of spinal Ago2 level, and overexpressing Ago2 significantly attenuated the pain hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ago2, not 1, 3, and 4, is downregulated in brain lysates from encephalomyelitis mice, the expression level of several miR-NAs, including let-7a-5p, let-7e-5p, let-7f-5p, 106b-5p, 144-3p, and 188a-5p, display a significant reduction (Lewkowicz et al, 2015), suggesting that Ago2 is involved in the etiology of CNS diseases (Savas et al, 2008). Deficiency of Ago2 in D2R neurons relieves self-administration of cocaine due to the declined content of miRNAs in the mouse striatum (Schaefer et al, 2010), revealing a vital role of Ago2 in the treatment of CNS diseases (Carrick et al, 2016). Here, we found that nociceptive behavior caused the decrease of spinal Ago2 level, and overexpressing Ago2 significantly attenuated the pain hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…A similar effect on inhibiting MPTP-induced apoptosis was observed by overexpressing miR-128 in mice . Dopamine receptors and the dopamine transporter have also been shown to be regulated by miRNA expression . It is, therefore, possible that the increased expression of protective miRNAs could be occurring in rrf-1 and rrf-3 mutants that are protecting the worms from MeHg-induced damage to dopaminergic signaling.…”
Section: Discussionmentioning
confidence: 73%
“…In the last years, it has been becoming clear that ncRNA dysregulation plays a critical role in the etiology of human neurological disorders. Actually, ncRNAs have emerged as potentially important players in this field; even more recent studies underline their pivotal roles in several neurological disorders, among which are schizophrenia [ 107 ], addiction [ 108 , 109 ], and depression [ 110 ], as already summarized in these previous reviews. Here, we will specifically focus on the current advances in ncRNA research involvements in PD.…”
Section: Noncoding Rnas Regulatory Network In Neurological Diseasementioning
confidence: 99%